TEMPORAL AND SPATIAL VARIATIONS OF PLASMA AND NEUTRAL VELOCITIES DURING SUBSTORM PERIODS. Issue 4 (July 2016) - Ding‐Wei, LIU; Hui, WANG; Tao, HUANG; Xue, CAO; Ke‐Deng, ZHANG
Abstract: This study statistically investigates the temporal and spatial variations of plasma convection velocity ( V y ) and thermospheric zonal wind velocity ( U y ) in the range of –4 hour (h) and +2 h MLT relative to substorm onsets (MLT onset) with both CHAMP and DMSP (F13, F15) satellites observations from 2001 to 2005. It shows that V y increase significantly in all MLT sectors and the latitudes of the peak values move equatorward in 1.5 h after substorm onsets. In the subsequent 1.5 h V y decrease in intensity and the peaks retreat poleward, which shows that the onsets of substorm can enhance the plasma convection velocity dramatically. The relative increase of V y is largest from –2 h to MLT onset, which indicates that the substorm mainly affects the thermosphere in the westward 0∼2 h MLT sector. U y increases steadily in 3 hours after substorm onsets, with a 1.5 h delay relative to V y in response to the substorm onsets.